2016
DOI: 10.1111/rda.12666
|View full text |Cite
|
Sign up to set email alerts
|

Successful Cryopreservation of Domestic Cat (Felis catus) Epididymal Sperm after Slow Equilibration to 15 or 10°C

Abstract: To support conservation strategies in wild species, simple but highly reproducible procedures of sperm cryopreservation are required for an application under field conditions. We used epididymal sperm of the domestic cat to optimize a sperm freezing procedure for felid species, particularly questioning the demand for sperm cooling to 4°C. We equilibrated sperm during slow cooling to only 15 or 10°C in a Tes-Tris-fructose extender with final concentrations of 4.7% (v/v) glycerol and 10% (v/v) of the water-solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…However, neither the percentage of total nor progressive motile lion sperm after thawing is satisfactory when compared with the outcome of cryopreservation in the domestic cat [16,30] or even more in farm animal species. Swanson [29] proposed a minimum of 10 × 10 6 motile sperm for one artificial insemination procedure in felids.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…However, neither the percentage of total nor progressive motile lion sperm after thawing is satisfactory when compared with the outcome of cryopreservation in the domestic cat [16,30] or even more in farm animal species. Swanson [29] proposed a minimum of 10 × 10 6 motile sperm for one artificial insemination procedure in felids.…”
Section: Discussionmentioning
confidence: 97%
“…A study from Crosier et al [31] on cheetah semen revealed that sperm exposure to glycerol for 1 hour at room temperature (∼22 °C) before a cooling phase of 3.5 hours to 5 °C had only a minimal effect on sperm motility after cryopreservation. In the light of this finding, we tested a procedure with a one-step addition of glycerol at ambient temperature, followed by a short equilibration on slow cooling for 40 minutes to only 15 °C before freezing, which had recently been proven to be successful with epididymal semen from the domestic cat [16]. After thawing, we determined 31.5 ± 14.1% (mean ± SD) motile lion sperm (median 31.0, range 2.2%-56.5%) for samples frozen in cryovials.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations